Legionella pneumonia associated with severe acute respiratory distress syndrome and diffuse alveolar hemorrhage - A rare association - Kashif, Muhammad (Respir Med Case Rep, 2017)
Legionella pneumophila is a common, usually underreported and undiagnosed cause of community acquired pneumonia which can lead to significant morbidity and mortality. Diffuse alveolar hemorrhage rarely have been associated with legionella infection. We present a 61-year-old man with hypertension, diabetes mellitus and obesity admitted with severe acute respiratory distress syndrome. He was found to have Legionella pneumonia with associated diffuse alveolar hemorrhage diagnosed with bronchoscopic sequential bronchoalveolar lavage. He was successfully managed with antibiotics, lung protective strategies and intravenous pulse dose steroids. This patient highlights the unusual association of Legionella infection and diffuse alveolar hemorrhage. Additionally, the case re-enforces the need for early and aggressive evaluation and management of patients presenting with pneumonia and progressive hypoxia despite adequate treatment.